2021
DOI: 10.1101/2021.06.01.446439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The human language system, including its inferior frontal component in ‘Broca’s area’, does not support music perception

Abstract: Language and music are two human-unique capacities whose relationship remains debated. Some argue for overlap in processing mechanisms, especially for structure processing, but others fail to find overlap. Using fMRI, we examined the responses of language brain regions to diverse music stimuli, and also probed the musical abilities of individuals with severe aphasia. Across four experiments, we obtained a clear answer: music does not recruit nor requires the language system. The language regions′ responses to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 269 publications
0
39
1
Order By: Relevance
“…Recent studies also found that parietal weighting was increased for tracking phoneme and word surprisal [54] as well as semantic tracking of speech for native speakers but not non-native speakers [55]. The parietal weighting could be indicative of language-specific processing in the posterior temporal lobe [56] which was recently shown to be absent when listening to music [57], but because the activations are broad and without source localization it is difficult to identify the location definitively. Still, there is some evidence that low-frequency tracking of speech may be produced by a domain-general mechanism [58].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also found that parietal weighting was increased for tracking phoneme and word surprisal [54] as well as semantic tracking of speech for native speakers but not non-native speakers [55]. The parietal weighting could be indicative of language-specific processing in the posterior temporal lobe [56] which was recently shown to be absent when listening to music [57], but because the activations are broad and without source localization it is difficult to identify the location definitively. Still, there is some evidence that low-frequency tracking of speech may be produced by a domain-general mechanism [58].…”
Section: Discussionmentioning
confidence: 99%
“…The results of neuroimaging and neuropsychological studies emphasize the difference between language, music, and action. For example, there are aphasic patients who show preserved ability for music processing (Chen et al, 2021;Slevc, Faroqi-Shah, Saxena, & Okada, 2016). There is a fronto-temporal core language network for 'highlevel' linguistic processing including syntactic processing which is not sensitive to music processing (Chen et al, 2021;Fedorenko, Behr, & Kanwisher, 2011).…”
mentioning
confidence: 99%
“…For example, there are aphasic patients who show preserved ability for music processing (Chen et al, 2021;Slevc, Faroqi-Shah, Saxena, & Okada, 2016). There is a fronto-temporal core language network for 'highlevel' linguistic processing including syntactic processing which is not sensitive to music processing (Chen et al, 2021;Fedorenko, Behr, & Kanwisher, 2011). The fronto-temporal network of language is left-lateralized, while that of music is right lateralized (Friederici, 2019).…”
mentioning
confidence: 99%
See 2 more Smart Citations